Self-injurious behaviour in patients with bipolar disorder and attention deficit hyperactivity disorder after central stimulant start– a retrospective study based on the lisie cohort. (13th April 2021) - Öhlund, L.; Ott, M.; Lundqvist, R.; Sandlund, M.; Renberg, E. Salander; Werneke, U.
Abstract : Introduction: Currently, our understanding remains limited of how co-occurring bipolar disorder and attention deficit hyperactivity disorder (ADHD) should be treated. Objectives: To evaluate the impact of central stimulant treatment on self-injurious behaviour in patients with a dual diagnosis of bipolar disorder or schizoaffective disorder and ADHD. Methods: Retrospective cohort study (LiSIE) into effects and side-effects of lithium as compared to other mood stabilisers. Here, using a mirror-image design, we compared suicide attempts and non-suicidal self-injury events within 6 months and 2 years before and after central stimulant treatment start. Results: Of 1564 eligible patients, 206 patients met inclusion criteria; having a dual diagnosis of bipolar disorder or schizoaffective disorder and ADHD at first central stimulant initiation. In these, suicide attempts and non-suicidal self-injury events decreased significantly within both 6 months (p = 0.004) and 2 years (p = 0.028) after central stimulant start. After multiple adjustments, this effect was preserved 2 years after central stimulant start (OR 0.63, 95% CI; 0.40 – 0.98, p = 0.041). Conclusions: Central stimulant treatment may reduce the risk of self-injurious behavior in patients with a dual diagnosis of bipolar disorder or schizoaffective disorder and ADHD. However, to reduce the risk of manic switches, concomitant mood stabilising treatment remains warranted. Disclosure: Michael Ott has been a scientific advisory board member of Astra Zeneca Sweden, Ursula Werneke has received funding for educational activities on behalf of Norrbotten Region (Masterclass Psychiatry Programme 2014–2018 and EAPM 2016, Luleå, Sweden): Astra